(NiSTORIQ POLIFONII(B.(NmNOGOGOLOSIE sREDNEWEKOW_Q (BX-XIV (NWEKAs (NwYP (B1.(NiSTORIQs - (Na(B.(NtREJSTERs (NREDAKTORs; (N`(B.(NeWDAKIMOWAs ((NmOSKWAs (NmUZYKAs, 1983)
(NnASTOQ]AQ KNIGA(B-(NPERWYJ WYPUSK iSTORII POLIFONII(B.s
Keywords: (NISTORIQs